Investigation of Effect of Machining Process Paramaeters on Surface Quality - Osman Hamdi Mete; Mehmet Şafak Baran (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Machining method is the most commonly used manufacturing method in the industry. The product, which is chipped on the raw material with the help of a cutting tool, is finalized. The manufactured product must be within the dimensional and geometric tolerances determined by the designer in order to discharge its functionality. In addition to these tolerances, surface quality is expected. In this study, the effect of the process parameters on the surface quality of the milling operation, which is the most commonly used machining method, was investigated as experimentally. Experimental design was carried out by using Taguchi L18 orthogonal array and the effect of four process parameters on the surface quality was investigated. ANOVA was carried out in order to investigate the effect of process parameters on experiment results and their statistical significance. The validity of experimental model was investigated by comparing the actual experimental results with the estimated results obtained by Minitab 19. According to Taguchi results; conventional cutting direction, 282 m/min. cutting speed, 0.15 mm/rev. feed rate and 0.5 mm cutting depth were found optimum levels of parameters. P value was found 0.00014 in ANOVA for feed rate parameter and it was found the most important parameter on the experiment results. R2 of experiment model was found % 91.4 according to comparison result.